Catalytic performance of bulk and La2O3-supported strontium oxide as a novel bifunctional catalyst for biodiesel production from sunflower oil - AL-Bayati, Ban B.; Ozdemir, Oguz Kaan; Khudhur, Ali G.; Ozdemir, Julide Hazal; Hantosh, Ahmed A.; Al-Sheikh, Farooq (TAYLOR & FRANCIS INC, 2026)
A SrO/La2O3 catalyst was prepared by physical ball-milling to improve stability and reusability in biodiesel production via transesterification. Characterization by XRD, FTIR, FESEM-EDX, and BET confirmed the catalyst properties. Optimized reaction conditions (Me: Oil ratio of 12:1, 1 wt% catalyst, 65 degrees C, 30 min) using the 3 SrO/La2O3 catalyst calcined at 800 degrees C achieved a maximum FAME yield of 98.6%. The catalyst maintained good reusability, with yield decreasing to 87% after three cycles. Biodiesel quality met ASTM D 6751 standards as confirmed by GC-MS and FTIR analysis. This work demonstrates the potential of SrO/La2O3 as a promising catalyst for efficient biodiesel synthesis.
Keywords: Biodiesel; biofuel; bifunctional; strontium oxide; transesterification; sunflower oil; WASTE COOKING OIL; HETEROGENEOUS CATALYST; METAL-OXIDE; DIMETHYL CARBONATE; OPTIMIZATION; SRO; COMBUSTION; ESTERIFICATION; SRO-ZNO/AL2O3; Thermodynamics; Science & Technology - Other Topics; Energy & Fuels